2012
DOI: 10.1152/ajprenal.00491.2011
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to maternal overnutrition and a high-fat diet during early postnatal development increases susceptibility to renal and metabolic injury later in life

Abstract: Overnutrition during pre- and postnatal development both confer increased susceptibility to renal and metabolic risks later in life; however, whether they have an additive effect on the severity of renal and metabolic injury remains unknown. The present study tested the hypothesis that a combination of a pre- and postnatal diet high in fat/fructose would exacerbate renal and metabolic injury in male offspring later in life. Male offspring born to high fat/high-fructose-fed mothers and fed a high-fat/high-fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
38
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 32 publications
10
38
1
3
Order By: Relevance
“…Similar to the observation that pups from fructose alone fed pregnancies are hyperinsulinaemic, 90 exposure to a highfat and high-fructose diet in utero and postnatally resulted in a 140% increase in plasma insulin levels compared with control offspring at 12 weeks of life and also increased blood glucose levels, although not significantly. 150 Fructose and saturated fatty acid (30% fructose, 9.9% coconut fat and 0.5% cholesterol) intake prior to pregnancy, throughout gestation and during lactation also results in increased fasting insulin and homeostatic model assessment (HOMA) levels in 3-month-old offspring fed a control diet from weaning. 79 This maternal hyperinsulinaemia and insulin insensitivity occurred without the development of obesity and, interestingly, epididymal and retroperitoneal fat depots were significantly smaller (18% and 44%, respectively) compared with control offspring.…”
Section: Interactive Effects Of Fructose Sucrose and Fat In The Matementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the observation that pups from fructose alone fed pregnancies are hyperinsulinaemic, 90 exposure to a highfat and high-fructose diet in utero and postnatally resulted in a 140% increase in plasma insulin levels compared with control offspring at 12 weeks of life and also increased blood glucose levels, although not significantly. 150 Fructose and saturated fatty acid (30% fructose, 9.9% coconut fat and 0.5% cholesterol) intake prior to pregnancy, throughout gestation and during lactation also results in increased fasting insulin and homeostatic model assessment (HOMA) levels in 3-month-old offspring fed a control diet from weaning. 79 This maternal hyperinsulinaemia and insulin insensitivity occurred without the development of obesity and, interestingly, epididymal and retroperitoneal fat depots were significantly smaller (18% and 44%, respectively) compared with control offspring.…”
Section: Interactive Effects Of Fructose Sucrose and Fat In The Matementioning
confidence: 99%
“…101,150 Providing a highfat diet with water containing 10% w/v fructose throughout pregnancy and lactation, followed by continuation of the diet in postnatal life, resulted in increased bodyweight and visceral fat, elevated blood glucose levels, glucose intolerance, a greater than twofold increase in urine albumin excretion and 60% increase in glomerulosclerosis in adult offspring compared with controls at 17 weeks of age. 101 Finally, it has been observed that a maternal 'junk-food' diet impacts the expression of key components of the mesolimbic reward pathway in the offspring of rat dams at 6 weeks and 3 months of age, with higher fat intake from weaning until at least 3 month of age.…”
Section: Interactive Effects Of Fructose Sucrose and Fat In The Matementioning
confidence: 99%
“…The offspring were fed their respective diets for 12 wk after weaning, making them 17 wk of age at the time of being euthanized. This time point was chosen based on our previous study in the male offspring (14).…”
Section: Experimental Designmentioning
confidence: 99%
“…However, the impact of postnatal overnutrition on adult renal function has not been fully examined. A study from our laboratory has recently shown that combined exposure to a high-fat/fructose diet during fetal and 17 wk of postnatal development potentiate the susceptibility of renal and metabolic disturbances later in life of the male offspring (14).…”
mentioning
confidence: 99%
“…Several rodent studies have taken a longer-term approach to determine the effects of overnutrition prior to, during gestation and during lactation on long-term kidney health. Feeding rats a high fat/high fructose diet from 6 weeks prior to mating, throughout pregnancy and subsequent lactation, resulted in offspring that developed albuminuria, which was exacerbated by postnatal overnutrition causing tubulointerstitial fibrosis and increased TGF-β expression (Jackson et al, 2012). In a separate study, inducing obesity in rats 5 weeks prior to mating results in the programming of increased adiposity in offspring, hyperleptinemia and hypertension in offspring in association with increased renal norepinephrine and increased renal renin expression (Samuelsson et al, 2010).…”
Section: Suboptimal Maternal Nutritionmentioning
confidence: 99%